(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the essence, goals and forms of differentiated education in higher education. It is emphasized that differentiation of learning makes it possible to ensure that all students master the content of education, which may be different for different students, but with the obligatory identification of a part that is invariant for all.